Benjamin Dwyer, Music Autopsies: Essays and Interviews (Hofheim: Wolke Verlag, 2023). ISBN 978-3-95593-138-4, 240 pp, €28.00 (paperback). - O'Leary, Martin (Journal of the Society for Musicology in Ireland, 2023)
A review of Benjamin Dwyer, Music Autopsies: Essays and Interviews (Hofheim: Wolke Verlag, 2023). ISBN 978-3-95593-138-4, 240 pp, €28.00 (paperback).